2021–2022 Florida Citrus Production Guide: Canopy Management: Chapter 19, CMG16/HS1303, rev. 4/2021 - Vashisth, Tripti; Zekri, Mongi; Alferez, Fernando (EDIS, 2021)
There were no changes in recommendation from the 2020–2021 edition.